Relationship between erythrocyte sedimentation rate and serum C-reactive protein in rheumatoid arthritis. Issue 4 (August 1979) - Walsh, L; Davies, P; McConkey, B
Abstract : Serum C-reactive protein (CRP) and the erythrocyte sedimentation rate (ESR) were compared in 241 patients with rheumatoid arthritis (RA). There was a positive linear correlation between the 2 measurements with a high degree of variability. Neither age nor duration of RA had a detectable influence. The relationship between CRP and ESR was, however, altered by treatment with gold, penicillamine, or high doses of prednisone. It is suggested that serum CRP is the more sensitive measurement, but that CRP and ESR do not have identical clinical significance.